Speech Characteristics of Modern Blogger (Based on the Material of Bloggers-Embroiderers of Russian Video Hosting YouTube): Речевая характеристика современного блогера (на материале блогеров-вышивальщиц российского видеохостинга You Tube) - Balakay, Anna (Przegląd Wschodnioeuropejski, 2019)
The article is devoted to the speech characteristic of the modern videoblogger. The author of the article chose the videoblogs of embroiderers broadcast on the Russian YouTube channel as a material for the study. Since every social role has its own set of language tools, it can be assumed that the speech of the videobloggers of the embroidery channel is characterized by a certain specificity. The particularities of the lexico-phraseological aspect of the speech of bloggers-embroiderers are considered in the article. Analysis is the subject to the professional borrowing, gaining wide positions in the lexical system of the modern Russian language. A special interest is the reinterpretation and the enlargement of the semantic structure of the usual names that generate individual metaphors by bloggers. The article also pays attention to positive, friendly tone of communication of videobloggers-embroiderers supported by the use of stable etiquette formulas.